Pelatihan dan Pendampingan Literasi Keuangan bagi Guru di Gugus V Mandara Giri Kec. Kubutambahan - Gede Widiadnyana Pasek; Kadek Prita Ary Astini; Ni Made Sri Ayuni; Mertyani Sari Dewi (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
There Group V Mandara Giri Kec. Kubutambahan is one of a collection of several elementary schools in the Kubutambahan District. Training in financial literacy is very important for every individual, one of which is the teachers in Cluster V Mandara Giri Kec. kubutambahan. Financial literacy really helps individuals to improve investment decisions, both in terms of the type of investment, where to invest, and the investment nominal that the individual will choose. This service is carried out through the Research and Community Service Center of the Satya Dharma College of Economics in collaboration with the Head of Cluster V Mandara Giri Kec. kubutambahan. In this community service activity, teachers in cluster V Mandara Giri Kec. kubutambahan, they were given financial literacy material, namely regarding investment. The results obtained from this activity can help teachers, in particular, to increase their understanding of financial literacy and investment decisions they have.